2021
DOI: 10.1002/marc.202100453
|View full text |Cite
|
Sign up to set email alerts
|

An Inspection into Multifarious Ways to Synthesize Poly(Amino Acid)s

Abstract: Poly(đœ¶-amino acid)s (PAAs) attract growing attention due to their essential role in the application as biomaterials. To synthesize PAAs with desired structures and properties, scientists have developed various synthetic techniques with respective advantages. Here, different approaches to preparing PAAs are inspected. Basic features and recent progresses of these methods are summarized, including polymerizations of amino acid N-carboxyanhydrides (NCAs), amino acid N-thiocarboxyanhydrides (NTAs), and N-phenoxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 163 publications
0
12
0
Order By: Relevance
“…1a, using our previously synthesized NIR-II small molecule TQF–NH 2 as the initiator, 43 a PSar-modified polymer (TQF–PSar) was successfully obtained with four dense and hydrophilic brush arms by ring-opening polymerization of sarcosine- N -thiocarboxyanhydride (Sar-NTA). 44–47 The 1 H-NMR spectrum demonstrated successful polymerization of PSar (Fig. S1†).…”
Section: Resultsmentioning
confidence: 96%
“…1a, using our previously synthesized NIR-II small molecule TQF–NH 2 as the initiator, 43 a PSar-modified polymer (TQF–PSar) was successfully obtained with four dense and hydrophilic brush arms by ring-opening polymerization of sarcosine- N -thiocarboxyanhydride (Sar-NTA). 44–47 The 1 H-NMR spectrum demonstrated successful polymerization of PSar (Fig. S1†).…”
Section: Resultsmentioning
confidence: 96%
“…[32,33,34] Among them, poly(amino acid)s (PAAs) have received widespread attention due to their simple and controllable synthesis, good biocompatibility and nontoxic metabolized products, flexible and adjustable functions, as well as the ability to fold into stable secondary structures. [35,36] Additionally, with the development of N-carboxyanhydrides (NCA) ring-opening polymerization (ROP) technology, [37,38] significant progress has been made in the regulation of secondary conformations of PAAs in recent years. [16,30] PAAs have been extensively studied as structural or functional materials such as nanoparticles, nanotubes, and hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the ring-opening polymerization (ROP) of α-amino acid N -thiocarboxyanhydrides (NTAs) becomes a fashionable way to synthesize tailored polypeptides or polypeptoids with a high MW. Although Kricheldorf et al found NTA and N-substituted NTA (NNTA) were not promising to synthesize high MW polypeptides and polypeptoids because of precipitation of polymers during polymerization and stabilization of thiocarbonate group by solvation, respectively, there have been many efforts paving the way for well-controlled ROP of NTA monomers. ,− Acetic acid (HAc) catalyzes polymerizations of NTA and NNTA to overturn common sense to the most extent because researchers used to think that HAc would inactivate the amino groups at the polymer chain end and impede propagation. Nevertheless, to the best of our knowledge, the copolymerization of NTAs and NNTAs has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%